2006
DOI: 10.1063/1.2367658
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet fast-response photoelectric effect in tilted orientation SrTiO3 single crystals

Abstract: Ultraviolet photoelectricity based on the vicinal cut as-supplied SrTiO3 single crystals has been experimentally studied in the absence of an applied bias at room temperature. An open-circuit photovoltage of 130ps rise time and 230ps full width at half maximum was observed under the irradiation of a 355nm pulsed laser of 25ps in duration. The dependence of the photoelectric effect on the tilting angles was studied, and the optimum angle is 20.9°. Seebeck effect is proposed to elucidate the tilting angle depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 17 publications
4
51
1
Order By: Relevance
“…The thermoelectric field leads to the separation of photogenerate carriers in the lateral direction and results the photovoltage we observed. Figure 2 shows the peak photovoltage V P L and peak photocurrent magnitude I P L dependence of the STO tilting angle α [20]. The experimental procedures are the same as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermoelectric field leads to the separation of photogenerate carriers in the lateral direction and results the photovoltage we observed. Figure 2 shows the peak photovoltage V P L and peak photocurrent magnitude I P L dependence of the STO tilting angle α [20]. The experimental procedures are the same as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we describe the recent advances and the future prospects of ultrafast photoelectric effects and high-sensitive photovoltages in the perovskite oxides and heterojunctions. Figure 1 shows a typical photovoltage pulse when a tilted 15 • SrTiO 3 (STO) single crystal is irradiated by a 355-nm pulsed laser with 25-ps duration at ambient temperature [20]. The inset of Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years, we have investigated the photoelectric effects under laser pulses in a variety of oxide heterostructures Zhao et al, 2005;Zhao et al, 2006a;Zhao et al, 2006b;Zhao et al, 2006c;Huang et al, 2006;Wen et al, 2009). It was found that the photoelectrical process is in a picosecond or nanosecond order in the oxide heterostructures, which opens up a door for the applications of oxide heterostructures in the optoelectronic detection devices.…”
Section: Transient Photoelectric Effectsmentioning
confidence: 99%
“…Strontium titanate (SrTiO 3 ), as an important perovskite conductor, has many potential applications in various microelectronic heterostructures [30], oxygen sensors [31], solar cells [32], and thermoelectric devices [33], due to its excellent dielectric, photoelectric, optical and catalytic properties. Moreover, SrTiO 3 with a band gap similar to that of titania, is also a very promising photocatalyst because of its superior photocorrosion resistibility, thermal stability, and easily doping to control the electrical properties [34][35][36][37].…”
mentioning
confidence: 99%